Comparison of Mamdani-Type and Sugeno-Type Fuzzy Inference Systems for Transformer Tap Changing System - Charles R. Sarimuthu; Vigna K. Ramachandaramurthy; H. Mokhlis; K.R. Agileswari (International Journal of Advances in Applied Sciences, 2016)
Voltage control is considered one of the basic operational requirements of electrical power systems. The most popular voltage control equipment includes On-Load Tap Changer (OLTC) transformer controlled by Automatic Voltage Control (AVC) relay. Recent studies have shown that fuzzy inference systems (FIS) are applicable for transformer tap changing system. In this paper, FIS are developed for transformer tap changing system using Mamdani-type and Sugeno-type fuzzy models. The results of the two fuzzy inference systems (FIS) are compared. The basic difference between the Mamdani-type FIS and Sugeno-type FIS is included in this paper. It also shows which one is a more suitable choice of the two FIS for transformer tap changing system.